Wound-Healing Potential of Rhoifolin-Rich Fraction Isolated from Sanguisorba officinalis Roots Supported by Enhancing Re-Epithelization, Angiogenesis, Anti-Inflammatory, and Antimicrobial Effects - Walaa A. Negm; Aya H. El-Kadem; Engy Elekhnawy; Nashwah G. M. Attallah; Gadah Abdulaziz Al-Hamoud; Thanaa A. El-Masry; Ahmed Zayed (MDPI AG, 2022)
A wound is a complicated bioprocess resulting in significant tissue damage, which is worsened by a secondary bacterial infection, commonly Pseudomonas aeruginosa and Staphylococcus aureus. The goal of our study was to investigate the metabolic profile and possible wound-healing effect of Sanguisorba officinalis roots rhoifolin rich fraction (RRF). The LC-ESI-MS/MS analysis of S. officinalis roots crude ethanol extract resulted in a tentative identification of 56 bioactive metabolites, while a major flavonoid fraction was isolated by column chromatography and identified by thin-layer chromatography coupled with electrospray ionization/mass spectrometry (TLC-ESI/MS), where rhoifolin was the major component representing 94.5% of its content. The antibiofilm activity of RRF on the mono-species and dual-species biofilm of P. aeruginosa and S. aureus was investigated. RRF exhibited inhibitory activity on P. aeruginosa and S. aureus mono-species biofilm at 2× minimum inhibitory concentration (MIC) and 4× MIC values. It also significantly inhibited the dual-species biofilm at 4× MIC values. Moreover, the wound-healing characteristics of RRF gel formulation were investigated. Rats were randomly allocated into four groups (eight rats in each): Untreated control; Blank gel; Betadine cream, and RRF gel groups. Animals were anesthetized, and full-thickness excisional skin wounds were created on the shaved area in the dorsal skin. The gels were topically applied to the wound's surface daily for 10 days. The results demonstrated that RRF had a promising wound-healing effect by up-regulating the platelet-derived growth factor (PDGF), vascular endothelial growth factor (VEGF), keratinocyte growth factor (KGF), and fibronectin, while metalloproteinase-1 (MMP-1), interleukin-6 (IL-6), IL-1β, and nitric oxide (NO) levels were suppressed. It also enhanced the immune staining of transforming growth factor (TGF-β) and improved histopathological findings. Furthermore, it displayed an immunomodulatory action on lipopolysaccharide-induced peripheral blood mononuclear cells. Hence, the wound-healing effect of rhoifolin was confirmed by supporting re-epithelization, angiogenesis, antibacterial, immunomodulatory, and anti-inflammatory activities.